Increasing the Efficiency of Underground Block Leaching of Metal - Yussupov, Khalidilla; Aben, Erbolat; Myrzakhmetov, Sayfulmalik; Akhmetkanov, Dalelkhan; Sarybayev, Nurzhigit (Civil Engineering Journal, 2024)
The purpose of this study is to increase the efficiency of underground block metal leaching by increasing the metal content in the pregnant solution using the cavitation effect. To achieve this goal, it is proposed to process (cavitate) the leaching solution on the injector. The following research methods were used in this study: analysis of the current state of scientific and technical problems and research, laboratory work to establish the effect of the treated (cavitated) solution on the metal content in the pregnant solution, collection and processing of statistical data from laboratory work, analysis of research results, and preparation of conclusions. According to the results of laboratory research, leaching with a treated solution on an injector leads to an increase in the content of a useful component in the pregnant solution. The maximum increase in the metal content in the pregnant solution was achieved by processing the leaching solution for 5 min. The effectiveness of the solution over time after treatment was maintained for a long time (up to one month). Changes in the solution pressure did not affect the effectiveness of the treated leaching solution. The scientific novelty of this work consists of determining the dependence of the content of the useful component in the pregnant solution on the time of processing the leaching solution on the injector and the leaching time, which determines the optimal time for processing the solution on the injector to obtain the maximum metal content in the pregnant solution. The dependence of the content of the useful component in the solution on the pressure during leaching with untreated and treated solutions on the injector was obtained. Doi: 10.28991/CEJ-2024-010-10-014 Full Text: PDF